أثر كتاب الأزهية للهروي في أمالي ابن الشجري (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
إنّ كتاب: الأزهية في علم الحروف لعلي بن محمد النحوي الهروي (ت 415هـ) هو كتاب قيّم في بابه، وذلك لما فيه من منهج دقيق، يتجلّى في وضوح تقسيمه، وتنوّع أمثلته، وفي ذكره لعدد أوجه الحرف واستعمالاته، وفي دقّة استقرائه. ولما كان هذا الكتاب قد صنّفه الهروي في باب الأدوات فقد أفاد منه أهل العلم الذين جاؤوا بعده، وفي مقدمتهم ابن الشجري الذي أكثر من النقل عنه ولا يكاد المرء يبالغ إن قال: إنّ جل ما جاء من أدوات في أمالي ابن الشجري إنما مردّه في الأعم الأغلب إلى كتاب الأزهية. غير أن ابن الشجري لم يصرح بأنه قد أفاد من كتاب الهروي على الرغم من أنه نقل عنه، وقد نقل عنه بطريقتين. الأولى وهي النقل بطريقة التلخيص، والثانية هي النقل الكلام بنصه أو قريباً من ذلك. وقد تتبع البحث هذه المواضع التي نقلها ابن الشجري عن الأزهية فقارنها وناقشها، وأظهر بالحجة والدليل أن ابن الشجري قد أفاد من كتاب الهروي في مواضع كثيرة من أماليه.     Al-Uzhiyeh Book in the Science of Letters by Ali Bin Mohammad Al-Nahawi Al-Hurawi (died 415h.) is a great book in its subject because of its accurate formulation which is apparent in the clarity of its divisions and the variety of its examples as well as in mentioning the number of methods the letter is used and its accurate follow up. A number of researchers have got a great benefit out of this book. one of those researchers is Ibn-Al-Shajari in his famous book named Amali of Ibn Al-Shajari. He quoted Al-Harawi” Book without mentioning such quotation. Ib elieve that he quotes Al-Harawi in two ways: First, in the method of briefing, and Second, he quoted his book word by word. However, I followed up the quotations he copied, Ibn Al-Shajari, comparing and discussing such quotations. I found evidence that Ibn Al-Shajari has quoted Al-Uzhiyeh’s Book in several places, of his Amalis.